The Effect of Entrepreneurship Education And Creative Thinking Towards Entrepreneurship Interest of Students Department of Economic Education, Faculty of Economics, Manado State University - Tamboto, Henry J.D; Ch.Manongko, Allen; Tarore, Johny (International Journal of Scientific Research and Management (IJSRM), 2022)
This study aims to determine the effect of entrepreneurship education and creative thinking on the entrepreneurial interest of students majoring in economic education at the Faculty of Economics, Manado State University. The method used is a survey research method with a sample of 73 students majoring in economics education, Faculty of Economics, Manado State University. Data collection is done by using questionnaires and documentation. The results of the study were analyzed using regression analysis method, with SPSS analysis tool. The results of this study indicate that partially entrepreneurship education has an effect on interest in entrepreneurship, creative thinking affects interest in entrepreneurship. Entrepreneurship education and creative thinking simultaneously affect the entrepreneurial interest of students majoring in economics education at the Faculty of Economics, Manado State University.